2022
DOI: 10.3390/antiox11122478
|View full text |Cite
|
Sign up to set email alerts
|

Role of FOXO3a Transcription Factor in the Regulation of Liver Oxidative Injury

Abstract: Oxidative stress has been identified as a key mechanism in liver damage caused by various chemicals. The transcription factor FOXO3a has emerged as a critical regulator of redox imbalance. Multiple post-translational changes and epigenetic processes closely regulate the activity of FOXO3a, resulting in synergistic or competing impacts on its subcellular localization, stability, protein–protein interactions, DNA binding affinity, and transcriptional programs. Depending on the chemical nature and subcellular con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 132 publications
0
4
0
Order By: Relevance
“…The DNA sequences designated as environmental response element are speculated to be involved in the induction of gene expression in response to hormonal signals or environmental stimuli [ 23 , 33 ]. Several transcription factors responsive to oxidative stress, including Forkhead transcription factor Fox L1 [ 34 ] and NF – kb (36) and AhR [ 35 ] were identified in the GSTe1 and GSTe2 promoters in both the resistant and susceptible strains of An. arabiensis .…”
Section: Discussionmentioning
confidence: 99%
“…The DNA sequences designated as environmental response element are speculated to be involved in the induction of gene expression in response to hormonal signals or environmental stimuli [ 23 , 33 ]. Several transcription factors responsive to oxidative stress, including Forkhead transcription factor Fox L1 [ 34 ] and NF – kb (36) and AhR [ 35 ] were identified in the GSTe1 and GSTe2 promoters in both the resistant and susceptible strains of An. arabiensis .…”
Section: Discussionmentioning
confidence: 99%
“…These factors play a role in liver function and disease (66). Furthermore, FOXO(s) play a critical role in protecting the liver against the development of NAFLD (67) and liver oxidative injury (68). In conclusion, the data indicates that tefluthrin exposure results in liver toxicity resulting in a transcriptomic response to mitigate the toxicity induced.…”
Section: Discussionmentioning
confidence: 99%
“…There are four elements in the FOXO sub-family: Namely, FOXO1, FOXO3a, FOXO4 and FOXO6. FOXO3a activity is regulated by post-translational modifications, such as acetylation, phosphorylation and ubiquitination (20). The results of a previous study revealed that histone deacetylases, such as Sirt1 and Sirt3, deacetylate FOXO3a and mediate its transcriptional activity (21).…”
Section: Tmf Suppresses Chondrocyte Hypertrophy In Osteoarthritic Car...mentioning
confidence: 99%